A contribution for the development of new resources selection models for the agile/virtual enterprises - Ávila, Paulo (2004)
The process of resources systems selection, takes an important part in Agile / Virtual Enterprises (A/V E) integration because the efficient resources selection, or resources systems selection, running in useful time and cost and with efficient solution, is an important operation within the A/V E design phase and certainly will contribute for the flexibility of an A/V E within the phase of its reconfiguration. The resources systems selection is a difficult matter to solve in A/V E because: it can be of exponential complexity resolution; it can be a multi criteria problem; and because there are different types of A/V Es with different requirements that have originate the creation of a specific resources selection model for each one of them. This kind of selection approach models will be reviewed from literature and analyzed its limitations and the consequent necessities of development new ones. At the first time we identified necessities that never were thought before, like performance measures for the selection model, and the necessities of identifying the sponsor for the selection process. We will see too that the models fit uniquely the requirements of a unique A/V E are rigid and not flexible enough to satisfy the requirements of another A/V E. These limitations that we highlight in this work are important to be considered in the development of new models and were simultaneously considered in the development of our selection model for the project of the BM_Virtual Enterprise.